Inhibitors of 11β-Hydroxysteroid Dehydrogenase Type 1 as Potential Drugs for Type 2 Diabetes Mellitus—A Systematic Review of Clinical and In Vivo Preclinical Studies - Almeida, Cristiana; Monteiro, Cristina; Silvestre, Samuel (Scientia pharmaceutica, 2021)
Diabetes mellitus is a pathology with increasing frequency in society, being one of the main causes of death worldwide. For this reason, new therapeutic targets have been studied over the years. 11β-hydroxysteroid dehydrogenase type 1 (11β-HSD1) is an enzyme responsible for reducing cortisone to its active form cortisol, which can lead to metabolic changes such as insulin resistance and hyperglycemia. Therefore, 11β-HSD1 inhibition may offer a new therapeutic approach for type 2 diabetes mellitus. This work intends to systematically review the available scientific evidence on this subject. For this, a search was conducted in three databases and 15 clinical and in vivo preclinical studies were included in this review. Despite the high inhibitory and selectivity levels achieved with several molecules and the demonstrated clinical efficacy in diabetes treatment, no phase III clinical trials have yet been conducted. This is important because the long-term effects of 11β-HSD1 inhibitors including the consequences in hypothalamic–pituitary–adrenal axis must be evaluated. However, this enzyme remains a promising target for drug development, including due to its effectiveness in controlling various factors that constitute the metabolic syndrome and its potential for multiple indications in patients with diabetes, including wound healing and weight loss.